Syphilis, blanchiment and French colonial medicine in sub-Saharan Africa during the interwar period - (:unkn) unknown (My University, 2023)
Abstract During the interwar period, France put unprecedented efforts into public health measures targeting the colonised populations of sub-Saharan Africa. This investment in health was seen as crucial to ensuring the renewal of the African labour force needed for the economic development of the colonies. Syphilis, although less deadly than other endemic or epidemic diseases such as yellow fever, sleeping sickness and bubonic plague, was one of the most widespread infections in France’s sub-Saharan colonies. This article demonstrates the contradictory nature of the colonial medicine approach to this disease during the interwar years. The negative impact of syphilis on population growth in Africa made it a major threat to the colonial project, and France put significant, costly investment into tackling the disease, focusing its efforts on maternal and child health. However, a closer look at syphilis control in sub-Saharan Africa reveals that the disease was also minimised as a public health issue, under-resourced and downplayed by colonial doctors and administrators. This neglect was embodied in the invention of a new colonial disease, ‘exotic syphilis’, which was presented as being a relatively benign skin disease among the African populations. It was also reflected in care practices, via a form of mass medicine based on the use of blanchiment , which consisted of knowingly limiting treatment to a superficial effect.
Keywords: African Research